Mass customization and footwear: myth, salvation or reality? a comprehensive analysis of the adoption of the mass customization paradigm in footwear, from the perspective of the EUROShoE (Extended User Oriented Shoe Enterprise) research project - Boër, Claudio Roberto. (Springer London, 2007)
Mass customization is an emerging paradigm that is gathering a growing interest in many different industrial fields. The EUROShoE project, financed by the European Commission, explored the applicability of and developed technologies for the adoption of such a paradigm in the footwear business. The three-year research made evident the benefits that shoe companies can obtain by switching to the new business models and contributed to the development of many of the enabling technologies involved in adopting the new paradigm. Mass Customization and Footwear: Myth, Salvation or Reality? is the only monograph dedicated to the application of mass customization in a particular industry. Based on the outcomes of the EUROShoE project, the book is a detailed analysis of the most relevant case studies of early mass customizers in the footwear sector, highlighting reasons for their failure or success. Both the technological aspects and the business aspects of mass customization, together with some relevant economic indicators are covered in the book. By showing examples of how a "mature" manufacturing sector like shoe making can be thoroughly renovated in business and mentality by applying this paradigm; Mass Customization and Footwear: Myth, Salvation or Reality? will interest both practitioners in the footwear sector and postgraduates, researchers and lecturers in the area of mass customization. Introduction: Why this Book and to Whom it is Addressed -- Mass Customization and Footwear -- The EUROShoE Project -- Footwear Mass Customization in Practice -- From Footwear to Other Industries -- Conclusion: A Few Questions to be Answered.